Effectiveness of Application Heat Transfer Practice Module in Retreading Technology - Tirta Maulana; Ikhwanul Qiram; Agung Nugroho; Hapsoro Condro Guritno (Journal of Educational Engineering and Environment, 2022)
The phenomenon of heat transfer is a science that must be learned by engineering students. Retreading process is one of the heat transfer phenomena in the process of repairing damage to rubber tires in vehicles. This study aims to reveal the effectiveness of the use of the heat transfer practicum module in the retreading process of the inner tube. This type of research is R and D, where the module contains several test parameters which include; surface pressure, heating temperature and time, and dimensions of the patched rubber compound. The 20 respondents selected for this study were mechanical engineering students at PGRI Banyuwangi University. The test includes aspects of the suitability of practical procedures and cognitive abilities in describing the process and mathematical solving of the heat transfer rate for each experimental parameter. The results show that the heat transfer module developed is quite feasible to use, this is based on the results of measuring the satisfaction of respondents in general, assessing it very well with an average of 59.8%. While on the aspect of learning effectiveness, it can be concluded that the practice module is included in the very effective category, where this is shown by increasing the percentage of respondents' abilities which are shown through changes in values before and after the implementation of the module.